Eco-Innovations and Initiatives of the Sofia Municipality for Green Jobs and Growth - Bozhikin, Ivan (Research Papers, 2021)
One of the crucial tools for achieving sustainable development and green growth are eco-innovation and green initiatives. They are the basis for the creation of new green sectors, activities, and green jobs. Therefore, the public sector and municipalities are increasingly striving to i) provide favorable conditions for the development of eco-innovations and their implementation in practice, and ii) to generate such innovations by themselves. The study aims to present the main eco-innovations and initiatives of Sofia Municipality in the period 2008-2019 to achieve green growth and green jobs. To accomplish this research goal is 1) study and analysis the important secondary documents in the study area and 2) analyzed information on eco-innovation and green growth in Sofia Municipality, provided by the Sofia Municipality experts. The main results of the study are indicated and discussed. The article ends with several summaries and conclusions.JEL: Q010